2012
DOI: 10.1105/tpc.111.092718
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Arabidopsis ARGONAUTE1-Mediated Slicing, Transgene-Induced RNA Silencing, and DNA Methylation by Distinct Domains of the Cucumber mosaic virus 2b Protein

Abstract: Unique among the known plant and animal viral suppressors of RNA silencing, the 2b protein interacts directly with both small interfering RNA (siRNA) and ARGONAUTE1 (AGO1) and AGO4 proteins and is targeted to the nucleolus. However, it is largely unknown which regions of the 111-residue 2b protein determine these biochemical properties and how they contribute to its diverse silencing suppressor activities. Here, we identified a functional nucleolar localization signal encoded within the 61-amino acid N-termina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
241
2
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(262 citation statements)
references
References 89 publications
12
241
2
7
Order By: Relevance
“…This interaction may also affect RNAPII processivity and abolish splicing of selected alternative exons (Ameyar-Zazoua et al, 2012;Li et al, 2012b;Alló et al, 2014). There have also been some suggestions that, in Arabidopsis, AGO1 localization is not limited to the cytoplasm (Ye et al, 2012;Duan et al, 2012). Using immunolocalization and western-blot analysis, we showed that AGO1 is indeed localized in the nucleus of Arabidopsis cells (Fig.…”
Section: Ago1 Cotranscriptionally Influences Pri-mirna Levels In Respmentioning
confidence: 74%
See 1 more Smart Citation
“…This interaction may also affect RNAPII processivity and abolish splicing of selected alternative exons (Ameyar-Zazoua et al, 2012;Li et al, 2012b;Alló et al, 2014). There have also been some suggestions that, in Arabidopsis, AGO1 localization is not limited to the cytoplasm (Ye et al, 2012;Duan et al, 2012). Using immunolocalization and western-blot analysis, we showed that AGO1 is indeed localized in the nucleus of Arabidopsis cells (Fig.…”
Section: Ago1 Cotranscriptionally Influences Pri-mirna Levels In Respmentioning
confidence: 74%
“…It has been demonstrated that miR168 is stabilized by AGO1 (Vaucheret et al, 2006;Vaucheret, 2009). The main role of Arabidopsis AGO1 as a slicer in the RISC complex that cuts an mRNA target places AGO1 in the cytoplasm where the cleavage of miRNA targets occurs, yet there are experimental data suggesting that AGO1 can also be localized in the nucleus in plant cells (Ye et al, 2012;Duan et al, 2012). However, the role of AGO1 in this cell compartment remains elusive.…”
mentioning
confidence: 99%
“…2b of CMV (CM95R strain) and TAV exhibit high affinity for long dsRNAs and ds-sRNAs Duan et al 2012;Gonzalez et al 2012;Goto et al 2007). CMV 2b (Fny and SD strains) was also shown to interact with AGO1 through the PAZ-and partly PIWI domains and blocks RISC slicer activity (Duan et al 2012;Zhang et al 2006).…”
Section: Targeting Multiple Steps Of Antiviral Pathwaysmentioning
confidence: 99%
“…2b interacts both with AGO4-related siRNAs and with AGO4 protein through PAZ and PIWI domains. The interaction with 2b reduces AGO4 access to endogenous target loci and consequently modulates endogenous transcription to create a favorable niche for CMV infection (Duan et al 2012;Gonzalez et al 2010Gonzalez et al , 2012Hamera et al 2012). P38 of TCV may also suppress silencing at multiple levels.…”
Section: Targeting Multiple Steps Of Antiviral Pathwaysmentioning
confidence: 99%
“…This viral protein has a dsRNA binding domain that is needed for RNAi suppression in vivo. Additionally, the CMV 2b protein appears to repress post-transcriptional gene silencing as well as RNA-directed DNA methylation by binding and sequestering siRNA and the long dsRNA precursor [29].…”
Section: Kshv and Innate Immunitymentioning
confidence: 99%